The geography of tourism and recreation : environment, place and space - Hall, Colin Michael, 1961- (Routledge, Taylor & Francis Group, 2014)
This fourth edition of The Geography of Tourism and Recreation provides students with a comprehensive introduction to the interrelationship between tourism, leisure and recreation from geographical and social science perspectives. It still remains the only book to systematically compare and contrast in a spatial context, tourism and recreation in relation to leisure time, offering insight into the demand, supply, planning, destination management and impacts of tourism and recreation. Whilst retaining its accessible style and approach this edition has been significantly updated to reflect recent developments and new concepts from geography which are beginning to permeate the tourism and recreational field.